¡Ahí está el detalle! - Cantinflas, 1911-1993; Alvarez, Sofia, 1915-1985; Bustillo Oro, Juan, 1904-; Camarillo, Dolores, 1910-1988; García, Sara, 1895-1980; Gómez Landero, Humberto; Pardavé, Joaquín, 1900-1955 (Vanguard Cinema, 2004)
Un vagabundo es confundido con un pariente perdido por mucho tiempo de una familia adinerada.